2021
DOI: 10.3390/en14102918
|View full text |Cite
|
Sign up to set email alerts
|

Methods of Stability Control of Perovskite Solar Cells for High Efficiency

Abstract: The increasing demand for renewable energy devices over the past decade has motivated researchers to develop new and improve the existing fabrication techniques. One of the promising candidates for renewable energy technology is metal halide perovskite, owning to its high power conversion efficiency and low processing cost. This work analyzes the relationship between the structure of metal halide perovskites and their properties along with the effect of alloying and other factors on device stability, as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 110 publications
0
3
0
Order By: Relevance
“…50,51 Most of these challenges in PSCs can be controlled through the proper design of the different device components to reduce the defects in the bulk and the interfaces between them. 52,53 The design of a perovskite AL with good bulk and surface properties is very important in improving the overall photophysical properties and structural integrity of PSCs. It plays a critical role in improving the quality of the interface with the CTLs and is therefore important in reducing the non-radiative recombination power losses and J-V hysteresis, and improving the stability of PSCs.…”
Section: Structure Properties and Working Principle Of Pscsmentioning
confidence: 99%
“…50,51 Most of these challenges in PSCs can be controlled through the proper design of the different device components to reduce the defects in the bulk and the interfaces between them. 52,53 The design of a perovskite AL with good bulk and surface properties is very important in improving the overall photophysical properties and structural integrity of PSCs. It plays a critical role in improving the quality of the interface with the CTLs and is therefore important in reducing the non-radiative recombination power losses and J-V hysteresis, and improving the stability of PSCs.…”
Section: Structure Properties and Working Principle Of Pscsmentioning
confidence: 99%
“…In [13,14], regularities were established, and it was shown that the presence of certain functional groups in the macromolecules of organic compounds led to the appearance of radiation absorption with a characteristic frequency. Such spectra made it possible, with a high degree of probability, to identify whether one particular absorption band belonged to one particular functional group present in the molecule.…”
Section: Methodsmentioning
confidence: 99%
“…Among various types of renewable energies/sources, solar energy has gained particular interest due to its inexhaustible and clean nature, which can be efficiently utilized by three main routes: photovoltaic cells, photocatalysis and solar-thermal power generation [ 1 , 8 , 9 , 10 ]. In particular, photovoltaic cells (solar cells) have received increasing attention and achieved significant progress in the past decades because of their direct and efficient transformation of sunlight energy into electricity [ 11 , 12 , 13 , 14 , 15 ]. Nowadays, the commercial photovoltaic markets are dominated by silicon-based solar cells, showing excellent stability and high PCE of 27.6% [ 16 ].…”
Section: Introductionmentioning
confidence: 99%